Investigation of Psycho-Social Variables Affecting the Professional Life of Persons after the Coaching Education - Doganer, Seckin; Akoglu, Halil Erdem (Asian Journal of Education and Training, 2020)
The aim of this research is to examine the effects of the coaches’ emotional labor behavior on emotional burnout and turnover intention. The research group consists of 201 coaches actively working in various sports centers in Ankara province. Personal information form consisting of demographic questions, “Emotional Labor Scale”, “Burnout Scale” and “Turnover Intention Scale” were used as data collection tools. In the research, after the normality test; Spearman Correlation and Multiple Regression analysis were performed on the data. The demographic information of the group participating in the study is given as a percentage table. According to the findings, as the knowledge and skill of the coach increases, emotional burnout, surface acting and turnover intention show decrease. At the same time, the increase of Professional success of the coaches causes emotional burnout, desensitization, surface acting and the turnover intention. It has been observed that the role of coaches, whose professional achievements have increased, has increased natural acting levels, but it has been determined that the role of deep acting has no effect on the turnover intention. As a conclusion, it was observed that burnout and turnover intention may decrease as the level of knowledge and skill increases in coaches. In addition, it was determined that surface acting behavior was not preferred by experienced coaches and mostly natural emotions were used.